Does stage of cancer, comorbidity or lifestyle factors explain educational differences in survival after endometrial cancer? A cohort study among Danish women diagnosed 2005–2009. (2nd June 2016) - Seidelin, Ulla Holten; Ibfelt, Else; Andersen, Ingelise; Steding-Jessen, Marianne; Høgdall, Claus; Kjær, Susanne Krüger; Dalton, Susanne Oksbjerg
Abstract: Background : Several studies have documented an association between socioeconomic position and survival from gynaecological cancer, but the mechanisms are unclear.Objective : The aim of this study was to examine the association between level of education and survival after endometrial cancer among Danish women; and whether differences in stage at diagnosis and comorbidity contribute to the educational differences in survival.Methods : Women with endometrial cancer diagnosed between 2005 and 2009 were identified in the Danish Gynaecological Cancer Database, with information on clinical characteristics, surgery, body mass index (BMI) and smoking status. Information on highest attained education, cohabitation and comorbidity was obtained from nationwide administrative registries. Logistic regression models were used to determine the association between level of education and cancer stage and Cox proportional hazards model for analyses of overall survival.Results : Of the 3638 patients identified during the study period, 787 had died by the end of 2011. The group of patients with short education had a higher odds ratio (OR) for advanced stage at diagnosis, but this was not statistically significant (adjusted OR 1.20; 95% CI 0.97–1.49). The age-adjusted hazard ratio (HR) for dying of patients with short education was 1.47 (CI 95% 1.17–1.80). Adjustment for cohabitation status, BMI, smoking and comorbidity did not change HRs, but further adjustment for cancer stage yielded a HR of 1.36 (1.11–1.67).Conclusion : Early detection in all educational groups might reduce social inequalities in survival, however, the unexplained increased risk for death after adjustment for prognostic factors, warrants increased attention to patients with short education in all age groups throughout treatment and rehabilitation.